MODEL JAM'IYYAH ASHWATUL MUTAMMIMAH DALAM MENUMBUHKAN BAKAT DAN MINAT TILAWAH SENI BACA AL-QUR'AN SANTRI DI PONDOK PESANTREN NGALAH PURWOSARI - Siti Husnia (STKIP Subang, 2026)
The development of students' talent and interest in Qur'anic tilawah requires a systematic learning model to improve recitation skills and encourage active participation in Qur'anic arts. This study aims to analyze the role of Jam'iyyah Ashwatul Mutammimah in fostering students' talent and interest in Qur'anic tilawah, describe the learning model implemented, and identify the supporting and inhibiting factors at Pondok Pesantren Ngalah Purwosari Pasuruan. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the learning model is implemented through regular training, talaqqi and mushafahah methods, maqamat instruction, vocal and breathing exercises, periodic evaluation, and participation in tilawah competitions. These activities significantly improve students' recitation skills, mastery of maqamat, vocal quality, self-confidence, and interest in tilawah. The program is supported by competent instructors, students' motivation, and institutional support, while limited training time and differences in students' abilities remain the main challenges. Keywords : Jam'iyyah Ashwatul Mutammimah, Qur'anic Tilawah, Talent and Interest, Islamic Boarding School.